HUBUNGAN ANTARA KEPERCAYAAN TERHADAP PEMIMPIN DENGAN KETERIKATAN KERJA PADA KARYAWAN PT TELKOM WITEL SEMARANG - Nabila Rahma Aidina; Unika Prihatsanti (Faculty of Psychology, Diponegoro University, 2017)
Work engagement is the ability of employees who are positive characterized by the physical and mental energy in the work and the involvement of a strong and full of concentration in work. Trust in leaders is the belief that the employee has toward the leader based on the belief that the leader is competent, integrity, consistence, loyal and open-minded. This study aims to determine the relationship between the beliefs of the leader with the engagement of work to the employees of PT Telkom Witel Semarang. The research populations that fulfill the characteristics of 171 employees, the research sample is 114 employees with the characteristics of working period of at least one year by using cluster random sampling technique. Data collection used a scale of work engagement (25 aitem α = 0.87) and a trust-to-leader scale (39 aitems α = 0.93). Simple regression analysis showed a positive and significant correlation between trust toward leader with working engagement (rxy = 0, 55 with <0,001), which means higher trust to leader, hence higher employee engagement. As well if the trust toward the leader is low then the engagement of work owned by employees will be low. Leadership trust contributes 30% to work engagement.